EVALUASI EFEKTIVITAS FUNGSI SATUAN PENGAWASAN INTERN (STUDI PADA PERUSAHAAN BUMN ) - ARDIANTO T., YUDHI (Berkala Ilmiah Mahasiswa Akuntansi)
Internal control is very important for all companies, especially the internal audit function. In the company's internal audit under the supervision of personnel who are called by the Internal Control Unit. SPI serves to provide information and advice to management in order to perform tasks well, so as to create an effective control. The purpose of this study was to determine the functions of the Internal Control Unit in BUMN. Type of data used in this study is qualitative data. Qualitative data analysis is used first, conducted a survey to the company. Second, make understanding the function of the Internal Control Unit within the company through the interview. Third, evaluate the effectiveness of the functions of the Internal Control Unit in BUMN. Fourth, draw conclusions on the evaluation of the effectiveness of the Internal Control Unit functions in BUMN. Based on research conducted, it can be concluded that outlines effective functioning of the Internal Control Unit in accordance with Quality Assurance Standards on internal review so that it can be said SPI has been effective in conducting internal audits.